Structural Mapping of Dike-Induced Faulting in Harrat Lunayyir (Saudi Arabia) by Using High Resolution Drone Imagery - Trippanera, Daniele; Ruch, Joël; Passone, Luca; Jónsson, Sigurjón (Frontiers in Earth Science, 2019)
Dike intrusions produce faulting at the surface along with seismic swarms and possible eruptions. Understanding the geometry and kinematics of dike-induced fractures can provide relevant information on what controls magma emplacement and the associated hazards. Here, we focus on the Harrat Lunayyir volcanic field (western Saudi Arabia), where in 2009 a dike intrusion formed a NNW-SSE oriented, ten-kilometer-long and up to one-meter deep graben. This widens from ~2 km in the SSE to ~5 km in the NNW, showing a well-defined border normal fault to the west but a diffused fracture zone to the east. We conducted a fixed-wing drone survey to create high resolution (3.4 cm) ortho-rectified images and DEMs of the western fault and of a portion of the eastern fracture zone to determine the fracture geometry and kinematics. We then integrated these results with field observations and InSAR data from the 2009 intrusion. Both fault zones contain smaller segments (hundreds of meters long) consisting of normal faults and extension fractures, showing two dominant orientation patterns: NNW-SSE (N330° ± 10°) and NW-SE (N300° ± 10°). The NNW-ESE oriented segments are sub-parallel to the inferred 2009 dike strike (N340°), to pre-historical Harrat Lunayyir eruptive fissures (N330°) and to the overall Red Sea axis (N330°). This suggests that these segments reflect the present-day off-rift stress field close to the Red Sea shoulder. However, the NW-SE oriented segments are oblique to this pattern and exhibit en–echelon structures, suggesting different processes such as: (1) a transfer (or soft-linkage) between dike-parallel fault segments, (2) a topographic control on the fault propagation and (3) a possible reactivation of inherited regional faults. Vertical fault offsets obtained by the drone survey along the western fault vary with the local lithology and these data are not consistent everywhere with the offsets derived from the 2009 InSAR measurements. Field evidence within lava flows also shows the occurrence of previous slipping event(s) on the fault before the 2009 intrusion. Collectively, we suggest that the mismatch between the drone and InSAR datasets is related to the different spatial and temporal resolutions offered by the two techniques.